Composition-dependent shuffle-shear coupling and shuffle-regulated strain glass transition in compositionally modulated Ti-Nb alloys. (1st March 2023) - Su, Yunting; Liang, Chuanxin; Sun, Xun; Zhang, Hualei; Liang, Qianglong; Zheng, Yufeng; Hao, Yulin; Yang, Rui; Wang, Dong; Banerjee, Dipankar; Wang, Yunzhi
Abstract: Athermal pure shuffle O′ nanodomains have been reported as a common structural state in metastable β-Ti alloys. In this study, by integrating thermodynamic databases, first-principles calculations, phase field simulations, and experiments, we reveal the coupling between the shuffle (O′) and shear (α″, orthorhombic martensite) nanodomains as a function of Nb concentration in Ti-Nb alloys. In particular, our first-principles calculations suggest a change in the phase transformation path from β → α″ to β → O′ as the Nb concentration increases, and our CALPHAD calculations based on the available thermodynamic database show a large metastable miscibility gap in Ti-Nb. Informed by these findings, our phase field simulations demonstrate how the O′ and α″ nanodomains form and evolve upon cooling in compositionally modulated Ti-Nb alloys produced by spinodal decomposition and the corresponding transformation behavior. Finally, our experimental characterization shows a continuous change of the shuffle component across the O′/α″ nanodomain boundaries. The novel microstructural states and their unique phase transformation path lead to an unprecedented continuous transformation behavior accompanied by superelasticity with almost zero hysteresis and small residual strain over a wide temperature range, all of which have been observed in the experiments. This unique transformation behavior upon cooling can be well characterized as a shuffle-regulated strain glass transition. This study could provide new insight in alloy design by utilizing composition-dependent shuffle-shear coupling during a structural phase transformation. Graphical abstract: Image, graphical abstract